Is cognitive emotion regulation mediating effects of childhood maltreatment on suicidal ideation: a cross-sectional retrospective study - Sabzehparvar, Mahtab; Amiri, Sohrab (Frontiers in Psychiatry, 2025)
BackgroundThis research aims to explore the impact of childhood maltreatment and cognitive emotion regulation strategies on suicidal ideation among adolescents. Additionally, it examines the mediating role of emotion regulation strategies in influencing suicidal ideation.MethodsThis cross-sectional study focused on adolescents aged 14 to 20 and involved participants selected through cluster sampling from secondary school levels, including both boys and girls. The research involved a sample size comprising 330 participants. The survey was conducted over a period from May 2024 to June 2024. The relationship between childhood maltreatment (exposure), cognitive emotion regulation (mediation), and suicidal ideation (outcome) was assessed using Pearson’s correlation coefficient. Additionally, structural equation modeling with maximum likelihood estimation was employed to examine the role of the mediator variable.ResultsChildhood maltreatment and maladaptive cognitive emotion regulation were identified as predictors of suicidal ideation, with Beta coefficients of 0.28 and 0.33, respectively. On the other hand, adaptive cognitive emotion regulation served as a protective factor against suicidal ideation, reflected in a Beta coefficient of -0.25. Additionally, the indirect pathways from childhood maltreatment to suicidal ideation via maladaptive and adaptive cognitive emotion regulation revealed partial mediation effects.ConclusionsEmotion regulation plays a mediating role in the link between childhood maltreatment and suicidal ideation. However, the impact of childhood maltreatment remains a significant factor in influencing suicidal thoughts. Prioritizing the mental health of children within health policies and screening efforts is therefore essential.